Designing English Matriculation Program as Competency Mapping Device for Sharia Banking Study Program Students - Fabianto, Eko (LPPM Universitas Pancasakti Tegal, 2018)
This research is a research and development (R & D) study. The procedures in conducting this research were held in some activities involving the lecturer and the students of Sharia Banking study program. Some activities will also involve some experts in certain fields, i.e. English materials expert and Sharia Banking expert. The objectives of this research study are: (1) to identify the needs in conducting a matriculation program for Sharia Banking study program which are developed; (2) to design the materials for Sharia Banking study program in accordance to the implementation of a matriculation program. Based on the findings on the needs, the matriculation program covers materials such as grammar review, and the four macro skills review. The materials provide relevant reviews which enable to show the competency of each students. In terms of the goal, it helps the students to accelerate their level to the required level to start the new semester. From research result, the average normalized gain shows up 0, 47 meaning that the design for matriculation program has an average effectiveness and can describe the competence level of Sharia Banking study program students. At last, this reference will be able to help in designing a matriculation program for Sharia Banking study program.